2009
DOI: 10.1016/s0091-679x(08)93016-8
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Intraflagellar Transport in Mammalian Primary Cilia

Abstract: The primary cilium is a specialized organelle that projects from the surface of many cell types. Unlike its motile counterpart it cannot beat but does transduce extracellular stimuli into intracellular signals and acts as a specialized subcellular compartment. The cilium is built and maintained by the transport of proteins and other biomolecules into and out of this compartment. The trafficking machinery for the cilium is referred to as IFT or intraflagellar transport. It was originally identified in the green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
1
16
1
Order By: Relevance
“…It unravelled the fastest IFT speed reported so far, especially for retrograde transport (Table 3). By comparing IFT data from multiple systems, we noticed a tendency for faster IFT in longer flagella (Table 3), a fact that is supported by the progressive increase in IFT (Engel et al, 2009;Dentler, 2005) during flagellar regeneration in Chlamydomonas or by faster anterograde IFT in IMCD cells incubated with compounds that trigger elongation of the primary cilium (Besschetnova et al, 2009). It should be noted that the predicted elapsed time for a complete IFT cycle is quite similar in all systems reported so far (10-13 s), with the noticeable exception of primary cilia in IMCD cells (Table 3).…”
Section: Ift In the Trypanosome Flagellummentioning
confidence: 80%
See 1 more Smart Citation
“…It unravelled the fastest IFT speed reported so far, especially for retrograde transport (Table 3). By comparing IFT data from multiple systems, we noticed a tendency for faster IFT in longer flagella (Table 3), a fact that is supported by the progressive increase in IFT (Engel et al, 2009;Dentler, 2005) during flagellar regeneration in Chlamydomonas or by faster anterograde IFT in IMCD cells incubated with compounds that trigger elongation of the primary cilium (Besschetnova et al, 2009). It should be noted that the predicted elapsed time for a complete IFT cycle is quite similar in all systems reported so far (10-13 s), with the noticeable exception of primary cilia in IMCD cells (Table 3).…”
Section: Ift In the Trypanosome Flagellummentioning
confidence: 80%
“…However, these observations are limited to few cell types (Follit et al, 2006;Absalon et al, 2008;Tran et al, 2008) and detailed investigation is only available for Chlamydomonas (Dentler, 2005) and for different types of ciliated neurons in C. elegans where unexpected differences have been reported (Snow et al, 2004;Morsci and Barr, 2011). Imaging IFT in mammals has been challenging and data have only been reported for the primary cilium of LLC-PK1 and IMCD cultured cells (Follit et al, 2006;Besschetnova et al, 2009). These studies revealed quite significant differences in IFT rates and in the nature of IFT anterograde motors and highlight the importance for further investigation in distinct cellular contexts.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been previously proposed that cilia length can be regulated through the modulation of retrograde and anterograde cargo trafficking along the axoneme (44,51). We have shown that CDK5 inhibition with either R-roscovitine or siRNA did not affect the velocities of the cargo trafficking, suggesting another mechanism must account for shortening of primary cilia length.…”
Section: Discussionmentioning
confidence: 99%
“…69 GCaMP3-positive cells were grown in MatTek chambers (35-mm petri dishes with a bottom coverslip insert) to 40%-50% confluency before serum starvation (0.5% FBS) (MatTek, No. 1.5).…”
Section: Cell Lines Rt-pcr and Western Blot Analysesmentioning
confidence: 99%